Design and Numerical-Method-Aided Optimization of a Novel Attachment System for Implant-Retained Dental Prostheses Using NiTi Shape Memory Alloys - Shayanfard, Pejman; Wendler, Frank; Hempel, Philipp; Karl, Matthias (Applied Sciences, 2023)
While nickel-titanium (NiTi) is the primary shape memory alloy (SMA) used in endodontic instruments, restorative dental components so far have not been fabricated from SMAs. The flexibility of these materials may solve problems in implant prosthodontics resulting from non-parallel implant positions and transfer inaccuracies. Based on a prototype of a novel attachment system for implant overdentures, a finite element model was created and used for studying different loading situations and design parameters followed by numerical analysis aided design optimization. The results revealed that the basic design of the attachment is capable of compensating misalignments of supporting implants as well as transfer inaccuracies of a clinically relevant magnitude by accommodating the large deformations induced under masticatory loading upon martensitic phase transformation at almost constant stress. The application of NiTi resulted in the reduction of the reaction forces recorded in the surrounding of the supporting implant, as well, the reaction forces between male and female parts of the attachment system could be reduced which will minimize wear phenomena and subsequent maintenance costs. These effects were seen to be enhanced in the optimized design.
CRIS-Team WoS Importer:2023-01-27

Finite Element Combined Design and Material Optimization Addressing the Wear in Removable Implant Prosthodontics - Shayanfard, Pejman; Tan, Xingchen; Karl, Matthias; Wendler, Frank (Journal of Functional Biomaterials, 2024)
Wear at the male–female interface of retentive elements in implant-supported removable prostheses is the most frequent complication in such applications. The lack of an ideal/optimal insertion path, as well as the fabrication inaccuracies, are the primary contributors to this issue. A male attachment with a common ball anchor enhanced by lateral flexibility was investigated as a solution, compared to the widely used rigid ball anchor design. A parametric finite element analysis was performed to compare the wear-inducing maximum strain at the female polymer counterpart by various attachment designs made from titanium and Nitinol. The evolution of mechanical strains causing wear in the female part, as well as the contribution of stresses and martensitic transformation in the implant’s flexible shaft, were evaluated under several insertion misfit scenarios. Results indicate that introducing a long flexible shaft in the titanium implant reduced maximum strains in the female attachment part by up to 61% as compared to the solid ball anchor. Further improvement was observed by using the shape memory alloy Nitinol as shaft material, leading to a minor reduction in stress and strain at the contact surface but allowing for a shorter abutment. Finally, the optimized Nitinol implant design with a short, necked flexible shaft promoting martensitic transformation at low plateau stress resulted in an approximate 90% reduction in maximum strains at the inner surface of the female part during manual insertion, which indicates a significantly reduced wear phenomenon at the contact.
CRIS-Team Scopus Importer:2024-12-06
Keywords: design optimization; finite element method; implant-supported removable prosthesis; material optimization; shape memory alloy; titanium; wear in female attachment part

Implant-Supported Overdentures: Current Status and Preclinical Testing of a Novel Attachment System - Wendler, Frank; Diehl, Lisa; Shayanfard, Pejman; Karl, Matthias (Journal of Clinical Medicine, 2023)
Numerous attachment systems exist for implant-supported overdentures, with each having specific limitations in terms of retention, cost, wear, maintenance and cleanability. A retrospective analysis of patients restored with implant-supported overdentures using bars, telescopic crowns and Locator-type attachments was performed and the patients were interviewed. An in vitro strain gauge study compared telescopic crowns, Locator-type attachments and a novel flexible attachment system employing a shape memory alloy (NiTi) with respect to peri-implant strain development during insertion, loading and removal of an overdenture. A significantly lower number of attachment-related complications was observed in bars as compared to telescopic crowns (p = 0.00007) and Locator-type attachments (p = 0.00000), respectively. Greater overall patient satisfaction was noted in bar-retained restorations while Locator-type attachments led to lower levels of satisfaction regarding prosthesis retention. In vitro, telescopic crowns caused maximum strain development during prosthesis insertion and loading, while during removal this was observed in Locators with white retentive inserts. NiTi attachments caused significantly lower strain development during insertion as compared to telescopic crowns (p = 0.027). During loading, NiTi attachments caused significantly lower strain development than Locators with blue retentive inserts (p = 0.039). During removal, NiTi attachments caused significantly less strain development as compared to Locators with white retentive inserts (p = 0.027). Positional discrepancies between male and female attachment parts affected the retention and reaction force between both components, which may be minimized by using the novel NiTi attachment system. This may be beneficial in terms of component wear and implant loading.
CRIS-Team Scopus Importer:2023-02-24
Keywords: complications; implant-supported overdenture; NiTi; patient satisfaction; retention; strain development; superelasticity; wear

Shape Memory Alloy (SMA) Damping for Smart Miniature Systems - Jacob, Kiran; Ahmadi, Shahabeddin; Shayanfard, Pejman; Wendler, Frank; Kohl, Manfred (Calm, Smooth and Smart: Novel Approaches for Influencing Vibrations by Means of Deliberately Introduced Dissipation, 2024)
Vibration damping and control using Shape Memory Alloy (SMA) foil based devices for miniature systems are presented. The high material hysteresis allows for energy dissipation up to 34 % for pseudoelastic and 86 % for one-way SMA material. Passive and active dampers are developed using SMA damper devices of single and double bridge structures and their performances are evaluated using a shock loading event. The dampers demonstrate high energy dissipation and achieve mass stabilization without any oscillation under vertical shock loading. A two-degree of freedom (2-DoF) vibration stabilization platform is developed using a monolithic SMA device, enabling ease of assembly. Operating frequencies up to 13 Hz are achieved, suitable for stabilization against vibrations in handheld devices, for eg., in smartphone cameras. Transient responses of damper devices to shock and harmonic loading are simulated based on 2D plane stress finite element models for SMA bridges, that well predict the measured mass displacement curves. The 2-DoF structures require multi-axial constitutive models that take into account the complex loading paths for spatially coupled movements.
CRIS-Team Scopus Importer:2023-10-06